2020
DOI: 10.1108/imds-09-2019-0460
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between organizational attitude and lean practices: an organizational sense-making perspective

Abstract: PurposePast studies of lean have failed to sufficiently address the importance of social factors for successful lean implementations. This paper aims to broaden and deepen the understanding of lean as a socio-technical paradigm by conceptualizing lean implementation as an organizational change process.Design/methodology/approachThis study draws on the organizational sense-making literature to conceptualize and validate lean implementation as an organizational change process that necessitates a focus on the abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…We follow Westland (2010) to determine the minimum sample size to detect effects by using the Soper (2016) calculator. The input parameter values for the Soper calculator (such as the anticipated effect size = 0.35, desired statistical power = 0.80 and probability level = 0.05) were borrowed from comparable studies such as Malik and Abdallah (2020). Based on the 22 observed variables representing four latent constructs, 94 was returned as a minimum sample by the Soper calculator and this study's final sample of 100 respondents exceeds this minimum requirement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We follow Westland (2010) to determine the minimum sample size to detect effects by using the Soper (2016) calculator. The input parameter values for the Soper calculator (such as the anticipated effect size = 0.35, desired statistical power = 0.80 and probability level = 0.05) were borrowed from comparable studies such as Malik and Abdallah (2020). Based on the 22 observed variables representing four latent constructs, 94 was returned as a minimum sample by the Soper calculator and this study's final sample of 100 respondents exceeds this minimum requirement.…”
Section: Methodsmentioning
confidence: 99%
“…Next, we checked for survey non-response bias and common method variance (CMV). A non-response bias test was performed by conducting a Mann–Whitney U test to detect statistically significant differences between early respondents and late respondents as a proxy for non-responders (Malik and Abdallah, 2020). The first quarter and last quarter of respondents did not reveal any statistically valid differences for the four theoretical constructs, implying that non-response bias was not a significant concern for our data (Chavez et al.…”
Section: Methodsmentioning
confidence: 99%
“…Attitude is pertinent to assumptions about the outcomes of a behavior and the appraisal of the proportion between the positive and negative degree of contributing to a learning action [57]. It has also been emphasized that a supportive organizational attitude is a precursor for the implementation of any lean improvement program [58]. Prior studies based on the TPB have confirmed the significant relationship between attitude toward behavior and behavioral intention [59,60].…”
Section: Theoretical Framework: Theory Of Planned Behavior (Tpb) and ...mentioning
confidence: 99%
“…In addition, flow management is not significant in small, medium, and large companies. The connection between internal awareness and the use of lean thinking was examined by Malik et al [34] and Amaro et al [35]. Their study's findings demonstrated that internal interactions inside an organization can enhance organizational awareness, and that this phenomenon has a big impact on how lean thinking is implemented in employee involvement, internal technology development, and customer management.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Malik and Abdallah [34] explored the relationship between organizational internal awareness and the practice of lean thinking. The study pointed out that the interaction between internal members of the organization contributes to the improvement of organizational awareness, and this phenomenon is important for employee participation and internal technology.…”
Section: Lean Production Concept and Applicationmentioning
confidence: 99%